KNOWLEDGE OF PEANUT FARMERS IN MOST IMPORTANT WEEDS DAMAGE THAT AFFECT THE CROP AND CONTROL METHODS IN JALOULA AREA/ DIYALA PROVINCE - Nseef, Lateef M.; Salmen, Mithal Abdulateef (Diyala Agricultural Sciences Journal, 2015)
The research aimed at determining the knowledge of peanut farmers in most important weeds damage that affect the crop and control methods in Jaloula area/ Diyala province. Also، to determine the knowledge of the farmers according to mechanical methods such as [ Flooding and tilling، hand pulling and mechanical pulling]، and chemical methods such as [ using herbicides before and after planting]. The research also aimed at knowing the farmers knowledge as related to some variables such as [ farmer's age، qualification، years of growing the crop، cultivated area، exposure to source of information]. The population included all the villages (20). The sample was randomly selected in ratio of (25%) of the villages (5) village with (150) growers. Then stratified randomly sample was selected of ratio (40%) from the farmers which was (60 farmers). A questionnaire has been designed to measure the independent factors mentioned above as well as measuring the knowledge level of peanut farmers concerning weeds damage and its control. The results showed that (53.3%) of respondents had low level of knowledge about weeds damage and its control. Moderate level in the axis such as [ flooding and tillage ، hand pulling and mechanical pulling] by (55%، 48.3%، 0.47%). There was low ratio concerning chemical control in using herbicides before planting (46.7%) and high ration in using herbicides after planting significant correlation be tween knowledge level and some independent factors [age، qualification، exposure to information]، and no significant relationship with [ income، years of cultivation، cultivated The researcher recommended to enter the peanut farmers in training program concerning weed damage and its control . Also، recommended that the Ministry of Agriculture should supply tools and herbicides to the farmers in easy ways